2009
DOI: 10.1002/hep.22639
|View full text |Cite
|
Sign up to set email alerts
|

Role of overexpression of CD151 and/or c-Met in predicting prognosis of hepatocellular carcinoma #

Abstract: It has been reported that tetraspanin CD151 acts as a promoter of metastasis in several tumors and plays an important role in c-Met/hepatocyte growth factor signaling. However, the role of CD151 alone and coexpression of CD151/c-Met in hepatocellular carcinoma (HCC) remains unclear. We found that expression of CD151 was positively related to metastatic potential of HCC cell lines, and modified cells with CD151 high showed higher secretion of matrix metalloproteinase 9 and aggressiveness in vitro and higher met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
238
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 202 publications
(249 citation statements)
references
References 38 publications
9
238
1
1
Order By: Relevance
“…Many studies have reported on the association between alterations in MET and poor prognosis and/or disease severity in human cancers (25)(26)(27)(28). These findings support the hypothesis that specific alterations in MET may provide predictive capacity for identifying patients most likely to benefit from MET inhibitor therapy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Many studies have reported on the association between alterations in MET and poor prognosis and/or disease severity in human cancers (25)(26)(27)(28). These findings support the hypothesis that specific alterations in MET may provide predictive capacity for identifying patients most likely to benefit from MET inhibitor therapy.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the HGF/MET signaling pathway has been shown to be activated during the genesis and progression of hepatocellular carcinoma. Many reports have highlighted the prevalence of MET gene and protein expression in hepatocellular carcinoma, and have investigated the role of MET signaling in hepatocellular carcinoma progression and maintenance (24)(25)(26)(27)(28). The importance of MET signaling in these processes suggests that the status of MET gene amplification and/or protein expression in patients with hepatocellular carcinoma may serve as potential biomarkers for prognosis or response to anti-HGF/MET therapy.…”
Section: Discussionmentioning
confidence: 99%
“…4 CD151, one of the most important of the tetraspanins, has been extensively studied, especially in connection with the progression and prognosis of malignant tumors, including breast cancer, colon cancer, prostate cancer, and HCC. [5][6][7][8] Initial evidence for the involvement of CD151 in metastasis came from a study that showed specific in vivo inhibition of metastasis in a human epidermoid carcinoma by an unknown antibody. Since then, reduction of CD151 expression in primary melanocytes by small interfering RNA (siRNA) has been shown to result in the loss of motility, whereas it has little effect on the steady-state levels of integrins.…”
mentioning
confidence: 99%
“…Clinically, high levels of CD151 are correlated with poor prognosis in a variety of tumours including epithelial malignancies such as carcinomas of the lung, 68 breast (invasive ductal carcinoma), 34,53,69 colon, 70 pancreas, 71 kidney, 10 prostate (PCa), 72 liver 73,74 and oesophagus (SCC), 75 as well as glioblastoma. 76 As in most cancers an elevated level of CD151 expression is associated positively with a high tumour grade (Table 1), the assumption that CD151 is involved in cancer progression is well grounded.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%
“…Indeed, overexpression of CD151 at the primary site was found to correspond with the development of metastases, mostly in lymph nodes. 53,71,[73][74][75] Formation of secondary tumours in distant organs such as lungs and bone was also noted in clear cell renal carcinoma (RCC). 10 CD151 is implicated as a potential diagnostic marker in osteosarcoma and prostate cancer.…”
Section: Clinical Aspects Of Cd151 Expressionmentioning
confidence: 99%